2022
DOI: 10.1590/1678-4499.20220056
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterotic pattern in relation to F1 performance of tropical and temperate-adapted sweet corn lines

Abstract: The aims of this study were: to assess the genetic relationship of supersweet corn populations; and to establish the heterotic pattern of 49 supersweet (sh2) corn inbreds on F2S5 generation based on molecular marker data and specific combining ability.Forty-nine inbreds were evaluated using 20 SSR molecular markers, which were allocated into heterotic groups according to the discriminant principal component analysis. Twelve inbreds were crossed in a complete diallel scheme. The 81 entries (hybrids developed, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While, at the other extreme, Ref. [50] found that the non-additive effects were higher than the additive ones for grain yield, cob weight, and CL for some genotypes [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While, at the other extreme, Ref. [50] found that the non-additive effects were higher than the additive ones for grain yield, cob weight, and CL for some genotypes [10].…”
Section: Discussionmentioning
confidence: 98%
“…To have an idea of the magnitude of the aforementioned research, the diallel designs proposed by Griffing can be used [8], which constitute a useful tool to characterize and estimate the capacity of GCA and SCA of parents and their crosses [9], as well as to define the most adequate method of genetic breeding to predict superior crosses and combine the best traits of the parents [10]. In this regard, various results have confirmed the utility of these designs in corn to estimate GCA and SCA, the GCA/SCA relation and the heterosis of the parents [2] and to classify them into heterotic groups based on the genetic expression of the traits studied [11], such as mesocotyl-coleoptile elongation [12], which carries out an important role in the emergence and development of a normal seedling [13], and the components of grain yield [3], which are crucial in corn yield.…”
Section: Introductionmentioning
confidence: 99%
“…Early evidence suggests that non-additive effects represent an important factor in the model, but these effects can also vary from one trait to another ( Zystro et al., 2021a , b ). For instance, Neto et al. (2022) indicate a significant impact of dominance on the SCA estimates in the performance of an F1 population, with a GCA/SCA ratio smaller than one unit for plant height, ear height, ear length, and kernel row number.…”
Section: Discussionmentioning
confidence: 99%